Utilização de sistemas, solar e eólico, no bombeamento de água para uso na irrigação - Nogueira, Cicero Urbanetto (2009)
In this work, it was made an applied research in two stations, the first one located at Canabarro locality and the second one at Politécnico School at UFSM, in Santa Maria city, RS, with wind and photovoltaic equipments for pumping water. These ones are used for fruit trees irrigation in irrigation systems of low pressure. The research work was developed from September 2007 to August 2009, when the results showed the viability of wind and photovoltaic equipments for utilization in the complementary irrigation in fruit cultures such as guava, fig and grape trees. In the fruit culture sector, are installed: one multivane fans windindicator one savonius windindicator and respective pumps as well as pump set and a photovoltaic board. With the photovoltaic system, the pumped volume was about 5000 m3/ha and, with the wind system, the pumped volume was approximately 6m3/ha. The wind groups demonstrated low efficiency, if compared to photovoltaic systems, which showed more efficient.